If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 2x^{2}+ -64 = 0 Reorder the terms: -64 + 2x^{2}= 0 Solving -64 + 2x^{2}= 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '64' to each side of the equation. -64 + 64 + 2x^{2}= 0 + 64 Combine like terms: -64 + 64 = 0 0 + 2x^{2}= 0 + 64 2x^{2}= 0 + 64 Combine like terms: 0 + 64 = 64 2x^{2}= 64 Divide each side by '2'. x^{2}= 32 Simplifying x^{2}= 32 Take the square root of each side: x = {-5.656854249, 5.656854249}

| x^2+9x=-9 | | 0.4(x-4)=10.0 | | 5=y+13 | | 10n=16 | | (2x^2-3)(6x+1)= | | -3-7= | | 7(6-29)=5(-3a+1) | | 2x^2*6x= | | -7-(-7)= | | -6x+12=-2(4x+1) | | (2j^2)*(6j)= | | -5+12=6b-3-5b | | 7-(-7)= | | 1-5(x+2)=9+x | | -15z+8=-14z+11 | | 2x-7x+6x-4x= | | 5(x-4)+9=2(x-4) | | 12+-13= | | -11x=154 | | 12a=14a-6 | | x^8-34x^4+225=0 | | 2y-13y=99 | | 6-6=16t-15t | | 2+(-12)-(-10)-8+(-19)= | | 2y-4y=16 | | 3-x=-14 | | -420=-20(-3b) | | 11-(x)=-14 | | -z=7 | | 11(-x)=-14 | | -14x=-11x+3 | | 100-92=40y-46y | | 11-(-x)=-38 | | 5(3-2x)=21 | | 8(x-3)=-3x+3 | | 112-88=28y-36y | | 8+4*a=40 | | 3d+5d+6d-6= | | -5(t-7)-(t+8)=5 | | -9s-4=8s-1 | | -12y-5x-7x= | | 9y=-15 | | -71+(-19)= | | 9x+5y=-33 | | (w-6)2= | | 0=-2(y+4) | | x+21+3x=-25-3x-31 | | 4x^2+2x-30=0 | | -12=12(h-3) | | 24-x=3(x+4) | | 6x=18-3x | | 2m=11 | | 20=6x-10 | | 3=9x | | 6(x+1.48)=5x | | -12(x-12)=-9(1+-7) | | 7(c-2)=8(c-3) | | X=2+3x | | -61+10y+2=3(5y-5)-9 | | -1.2=-0.5u+0.1u | | 8x-3y=19 | | -12(x-12)=-9(1+-7x) | | 5x+7=-8 | | -7(4p+3)-49=2(5p+3) | | 3t+4+t=16 |